Palladium/copper-catalyzed arylation of alkenes with N′-acyl arylhydrazines. (23rd December 2016) - Zhang, Ji-Quan; Cao, Jun; Li, Wei; Li, Shu-Min; Li, Yong-Kang; Wang, Jian-Ta; Tang, Lei
Abstract : An efficient and ligand-free palladium/copper-catalyzed Heck-type coupling reaction of N ′-acyl arylhydrazines with olefins for the practical synthesis of arylalkenes. Abstract : A novel ligand-free palladium/copper-catalyzed Heck-type coupling reaction of alkenes and N ′-acyl arylhydrazines has been developed by using air as the terminal oxidant. This protocol features wide functional group tolerance and produces highly chemoselective and regioselective products with good to excellent yields.